Off-Cycle and Out of Sync: How Election Timing Influences Political Representation. Issue 4 (30th December 2021) - Hartney, Michael T.; Hayes, Sam D.
Abstract: States exert significant control over many different types of electoral institutions that influence the tone and direction of political representation in American democracy. Yet almost nothing is known about the consequences of the institution that has the greatest singular impact on the turnout and composition of the electorate: election timing. We argue that off-cycle elections will tend to produce governments that are not well-aligned with the political preferences of their median constituent. To empirically test this expectation, we examine the relationship between election timing and mass–elite congruence across local school district governments. Leveraging variation in election timing across districts within the same state, we find that board members are more likely to hold political preferences that are aligned with their constituents when boards are elected in on- versus off-cycle races. We conclude by discussing the implications of these findings for the study of representation and election timing, suggesting some possible avenues for future research.